2014
DOI: 10.1016/j.seizure.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of employees of service and trading companies towards people with epilepsy and their professional activity in Poland

Abstract: To improve the employment situation of people with epilepsy, knowledge among workers should be increased. This should be done at various levels of employment to ensure that the risks of employing a person with epilepsy are more adequately assessed and mitigated if possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…In the workplace, negative attitudes towards PWE are also evident. 5; 47 Jacoby 5 reported that for employees, working with a PWE would cause great concern, second to working with a person suffering from stress or depression. Studies seemed to indicate that while the general population did not typically voice stigmatizing ideas or thoughts, their attitudes indicate recognition that stigma exists.…”
Section: Resultsmentioning
confidence: 99%
“…In the workplace, negative attitudes towards PWE are also evident. 5; 47 Jacoby 5 reported that for employees, working with a PWE would cause great concern, second to working with a person suffering from stress or depression. Studies seemed to indicate that while the general population did not typically voice stigmatizing ideas or thoughts, their attitudes indicate recognition that stigma exists.…”
Section: Resultsmentioning
confidence: 99%
“…To help with the interpretation of the results, the overall KAP score has been transformed into several categories. They consisted in 7 classes [31] : Excellent (26)(27)(28)(29), Very good (23)(24)(25), Good (20)(21)(22), Fairly good (17)(18)(19), Fair (15)(16), Low (12)(13)(14), Nil (0-11). The Excellent range was considered as the reference level of knowledge.…”
Section: Instrumentmentioning
confidence: 99%
“…Public awareness and attitudes towards epilepsy differ across cultures [1][2][3][4][5][6]. It has been noted that traditional beliefs and lack of knowledge strongly influence attitudes towards epilepsy [1][2][3]5].…”
Section: Introductionmentioning
confidence: 99%